Gae Aulenti (1927-2012) - worlds exhibition guide - Agosti, Giovanni 1961-; Artioli, Nina; Boeri, Stefano 1956- (Electa, 2024)
Written by Giovanni Agosti, this guide charts the Triennale Milano exhibition on Gae Aulenti (1927- 2012), affording insights into its critical and cultural underpinning. In parallel, it provides an overview of the rules of the game on which the Tspoon studio based the mis-enscène of the exhibition: an almost cubist reconstruction of a number of the spaces created by the architect, following a chronological sequence that encompasses everything from exhibition designs, shops and apartments to stage sets, museums, subways and airports, spanning the period 1964-2012, from the years of Italy’s economic boom right through to its recent history. The book also includes a list of the works on display, a short biography of Gae Aulenti and a selected annotated bibliography. The guide is accompanied – both physically and conceptually – by two other products: a deck of cards, which highlights the key figures in the various worlds with which the architect engaged; and the full exhibition catalogue, which features an illustrated chronology and an extensive list of over 700 works, as well as an in-depth account of the exhibition itself
Impressum: "Gae Aulenti (1927-2012)", 22 May 2024 - 12 January 2025
Keywords: Aulenti, Gae -- 1927-2012; Ausstellungskatalog -- Triennale Milano -- 22.05.2024-12.01.2025 -- Mailand; Bildband